Literature Study of Soil Transmitted Helminths (STH) Infections in Children: Laboratory Examination and Mortality Risk - Agnes Cecilia; Ahmad Abid Syarif; Arya Jagad Mulawarwan; Herciella Bernadetha; Joice Earlene Nathaniella Taffy; Rezjita Asti Pratiwi (Tropis: Jurnal Riset Teknologi Laboratorium Medis, 2026)
Soil-Transmitted Helminth (STH) infections represent a global health problem, imposing a substantial burdenon children due to poor sanitation. This literature review aims to analyze laboratory examinations in STH infectionsamong children and their association with mortality risk. The study employed a Systematic Literature Review methodthrough searches in PubMed, ScienceDirect, and Google Scholar using relevant keywords, restricted to publications fromthe past ten years. The findings indicate that Ascaris lumbricoides frequently causes acute complications such asmechanical asphyxia and intestinal obstruction, which may lead to death if not promptly managed. Trichuris trichiurainfection can result in chronic complications including dysentery syndrome, severe anemia, stunting, and malnutrition,all of which increase the risk of mortality in children. Meanwhile, hookworm infection may lead to severe anemia andhypoalbuminemia in children. Laboratory examinations such as stool microscopy, histopathology, radiology, andultrasonography are essential for establishing diagnosis, assessing disease severity, and guiding therapy. In conclusion,early detection of STH infections through laboratory investigations plays a critical role in preventing seriouscomplications and reducing mortality risk in children, underscoring the need for strategies that extend beyond dewormingprograms to include nutritional improvement and the management of comorbid conditions.